2013
DOI: 10.11646/zootaxa.3682.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovered at last: a new enigmatic genus of Axymyiidae (Diptera) from western North America

Abstract: An unusual and undescribed genus and species of Axymyiidae known from a single specimen collected more than 50 years ago in Alaska is rediscovered in Mt. Rainier National Park (USA: WA). Based on two female specimens, Plesioaxymyia vespertina gen. nov., sp. nov. is described. A preliminary phylogenetic tree of the Axymyiidae is presented, showing Plesioaxymyia as sister group to all remaining axymyiid genera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The correct response is to confess that there is not sufficient evidence to resolve such a group (or particular nodes). It should be kept in mind that for the vast majority of Diptera, our knowledge of morphology (external and internal) is extremely limited (Wheeler, 2008b) and there are huge research opportunities for detailed study to provide more (and better understood) characters for further phylogenetic analysis (e.g., Brown et al, 2015;Sinclair, 2013;Tachi, 2014;Wipfler et al, 2012). So too, some distinctive genes or characters within them can be understood as synapomorphies.…”
Section: Genomes Vs Phenotypementioning
confidence: 99%
“…The correct response is to confess that there is not sufficient evidence to resolve such a group (or particular nodes). It should be kept in mind that for the vast majority of Diptera, our knowledge of morphology (external and internal) is extremely limited (Wheeler, 2008b) and there are huge research opportunities for detailed study to provide more (and better understood) characters for further phylogenetic analysis (e.g., Brown et al, 2015;Sinclair, 2013;Tachi, 2014;Wipfler et al, 2012). So too, some distinctive genes or characters within them can be understood as synapomorphies.…”
Section: Genomes Vs Phenotypementioning
confidence: 99%
“…Placement of the family within one of the nematoceran infraorders remains controversial, although the family is most commonly placed in either a variably defined Bibionomorpha (Oosterbroek & Courtney 1995;Wiegmann et al 2011) or within the superfamily Axymyioidea (Mamaev & Krivosheina 1966) or the infraorder Axymyiomorpha (Wood & Borkent 1989), which includes either the family Axymyiidae alone, or includes Axymyiidae, Perissommatidae, and Pachyneuridae (Hennig 1973;Amorim 1992). Considering that the infraordinal placement of axymyiids remains unresolved it is no surprise that the sister group to Axymyiidae also remains controversial (Wood & Borkent 1989;Fitzgerald 2004;Blagoderov et al 2007;Bertone et al 2008;Borkent & Sinclair 2012;Sinclair 2013;Sinclair et al 2013;Schneeberg et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Now most authors agree with a separate family status suggested by MAMAEV & KRIVOSHEINA; its infraorder position is debatable, however: Tipulomorpha (ROHDENDORF 1946), Bibionomorpha (HENNIG 1968, SHCHERBAKOV et al 1995, WIEGMANN et al 2011 or Axymyiomorpha (WOOD & BORKENT 1989, KOVALEV 1989, KRZEMIŃSKA et al 1993, KRZEMIŃSKI & KRZEMIŃSKA 2003. Recently, axymyiids became a focus of attention as the subject of studies on morphology, life history and fossils (ZHANG 2004, 2010, WIHLM & COURTNEY 2011, BORKENT & SINCLAIR 2012, WIHLM et al 2012, SINCLAIR 2013, SCHNEEBERG et al 2013. The family has been used as example taxa in recent phylogenetic studies, but the results of these provide no definite evidence for phylogenetic relationships of Axymyiidae to the other nematocerous families (BERTONE et al 2008, SCHNEEBERG et al 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the Axymyiidae include four extant genera (Axymyia, Mesaxymyia MAMAEV, 1968, Protaxymyia MAMAEV & KRIVOSHEINA, 1966, Plesioaxymyia SINCLAIR, 2013) with eight described species, known from the Holarctic Region, Taiwan and southern China (ISHIDA 1953, MAMAEV & KRIVOSHEINA 1966, MAMAEV 1968, YANG 1993, PAPP 2007, SINCLAIR 2013. In addition, three monotypic genera are known from the Jurassic of Asia (Psocites (HONG), Juraxymyia ZHANG, and Sinaxymyia ZHANG, ZHANG 2010).…”
Section: Introductionmentioning
confidence: 99%